IMPLEMENTASI LITERASI MEDIA DALAM PENGEMBANGAN KONTEN DIGITAL RAMAH ANAK : STUDI KASUS PLATFORM YOUTUBE KIDS INDONESIA - Mutiara Dara Utama; Melvia Tentua (JURNAL BADATI, 2023)
This research aims to analyze the implementation of media literacy in developing child-friendly digital content on the YouTube Kids Indonesia platform. Using a qualitative approach with case study design, the research was conducted through in-depth interviews with 30 informants consisting of YouTube Kids Indonesia team members, content creators, media literacy experts, children's media observers, and active parent users. Data collection was also carried out through participant observation for six months and related document analysis. The results show significant improvement in the implementation of media literacy components from 2021-2024, with technical ability reaching 85%, critical understanding 80%, and creative production 70%. Content distribution is still dominated by entertainment (40%) and educational content (35%), while the moderation system shows high effectiveness in detecting violent content (95%) but relatively lower for culturally nuanced content (75%). The identified implementation model demonstrates effective integration between technical systems and educational aspects, although it still requires development in terms of local cultural context sensitivity and content balance.